Matched case-control study evaluating the frequency of the main agents associated with neonatal diarrhea in piglets - Ricardo T. Lippke; Sandra M. Borowski; Sandra M.T. Marques; Suelen O. Paesi; Laura L. Almeida; Andrea M. Moreno; Luís G. Corbellini; David E.S.N. de Barcellos (Pesquisa Veterinária Brasileira, 2011)
A case-control study was carried out in litters of 1 to 7-day-old piglets to identify the main infectious agents involved with neonatal diarrhea in pigs. Fecal samples (n=276) from piglets were collected on pig farms in the State of Rio Grande do Sul, Brazil, from May to September 2007. Litters with diarrhea were considered cases (n=129) and normal litters (n=147) controls. The samples were examined by latex agglutination test, PAGE, conventional isolating techniques, ELISA, PCR, and microscopic methods in order to detect rotavirus, bacterial pathogens (Escherichia coli, Clostridium perfringens type A and C, and Clostridium difficile), and parasites (Coccidian and Cryptosporidium spp.). Outbreaks of diarrhea were not observed during sampling. At least one agent was detected in fecal samples on 25 out of 28 farms (89.3%) and in 16 farms (57.1%) more than one agent was found. The main agents diagnosed were Coccidia (42.86%) and rotavirus (39.29%). The main agents identified in litters with diarrhea were Clostridium difficile (10.6%), Clostridium perfringens type A (8.8%) and rotavirus (7.5%); in control litters, Clostridium difficile (16.6%) and Coccidian (8.5%). Beta hemolytic Escherichia coli and Clostridium perfringens type C were not detected. When compared with controls, no agent was significantly associated with diarrhea in case litters. These findings stress the need for caution in the interpretation of laboratorial diagnosis of mild diarrhea in neonatal pigs, as the sole detection of an agent does not necessarily indicate that it is the cause of the problem.